Crystal structure of 4-methoxy-N-[(pyrrolidin-1-yl) carbothioyl]benzamide - Suhud K.; Heng L.Y.; Hasbullah S.A.; Ahmad M.; Kassim M.B.; Stoeckli-Evans H. (International Union of Crystallography, 2024)
In the title compound, C13H16N2O2S, the pyrrolidine ring has a twisted conformation on the central - CH2-CH2- bond. Its mean plane is inclined to the 4-methoxybenzoyl ring by 72.79 (15)°. In the crystal, molecules are linked by N - H⋯O and C - H⋯O hydrogen bonds to the same O-atom acceptor, forming chains along [001]. The chains are linked via slipped parallel π-π interactions [inter-centroid distance = 3.7578 (13) Å], forming undulating slabs parallel to (100).